Influência dos glicosaminoglicanos na interação das proteínas do sistema calicreína-cinina plasmático na superfície celular - Melo, Kátia Regina Brasil [UNIFESP] (2006)
The kallirein-kinin system comprises low and high molecular weight kininogens (LK and HK), tissue and plasma kallikreins, and was first recognized as a plasma and tissue proteolytic system responsible for bradykinin (BK) release. The main function of kininogens has been described as precursors of BK, a peptide which is not active unless it is released from kininogens. The plasma kallikrein-kinin system is related to vascular biology and it is involved and interacts with different systems such as coagulation, fibrinolysis, complement and renin-angiotensin systems. HK is a multidomain protein with antithrombin, antiadhesive and profibrinolytic activities. Recent studies have revealed that HK free from BK (HKa) inhibits angiogenesis while BK promotes angiogenesis. In blood and vascular cells some different proteins have been described as HK binding receptors: Mac-1 integrin (aMb-2 or CD11b/CD18) on granulocytes, the receptor that binds to the globular “heads” of C1q (p33/gC1qR), cytokeratin 1 (CK1) and urokinase plasminogen activator receptor (uPAR) on HUVECs, and glycoprotein Ib-IX-V and thrombospondin on platelets. More recently both heparan sulfate and chondroitin sulfate have been described as HK putative receptors. The aim of this work was to study the influence of glycosaminoglycans (GAGs) on HK binding to cell surface and lysates and its processing using two different Chinese hamster ovary cell lines, CHO-wild type (CHO-K1) and CHO-745 (mutant) which is deficient in the synthesis of proteoglycans (PGs) due to lack of activity of xylosyl transferase. Biotin-HK (b-HK) bound to CHO-K1 cell surface in Zn2+ dependent manner. The b-HK level of binding was much higher on cell surfaces comparing to lysates from both cell lines and this binding was not reversible by 20 fold molar excess of unlabeled HK at both CHO-K1 and CHO-745. At 37°C the Bmax values for both CHO-K1 and CHO-745 are very similar but the Kdap for HK binding to CHO-K1 is 4.4 times higher comparing to CHO-745 suggesting that the presence of PGs/GAGs impair HK interaction with other putative receptors on cell surface. Considering the Bmax determinations at 4°C on CHOFor K1 it is 3.0 times lower comparing to Bmax at 37°C and on CHO-745 the Bmax value at 4°C is 1.4 times lower comparing to Bmax at 37°C. The difference of Bmax values at both temperatures for each cell line suggests that HK is internalized and confocal microscopy experiments detected HK internalized only on CHO-K1. Plasma prekallikrein (PK) bound to both cell lines in the presence of HK; however, in the absence of HK PK also bound only to CHO-K1 cell surface suggesting that PGs/GAGs may interact with PK. Once HK/PK complex is assembled on cell surface and lysates of both cell lines PK turns to plasma kallikrein (huPK) and both prolylcarboxypeptidase (PRCP) and cathepsins may participate in this process. The intact HK assembled to cell surface and lysates of both cell lines and in the absence of PK/huPK is cleaved in one site and probably PRCP or tissue kallikrein may process HK in this circumstances. The cell membrane interaction of plasma kallikrein-kinin system proteins through binding and internalization can result in liberation of HK fragments and huPK pericellular activity which may influence in pathological and physiological process.